PROBLEMS OF STUDYING SOMATIC EXPRESSIONS IN MODERN LINGUISTICS - Xamdamova Gulshan Xamroyevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the phraseological aspect of modern linguistics, history, and the formation of phraseology. It is also studied by the use of somatics in phraseology in modern linguistics.